The Persengketaan Laut Mediterania Rivalitas Turki-Yunani - Yoel, Grevildo Austhin (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Abstract In this article, the author seeks to examine the Mediterranean Sea dispute, which has been disputed by Turkey and Greece since tensions between the two sides escalated in August 2020, when Turkey sent a ship to explore the eastern Mediterranean waters claimed by Greece. To examine this issue, the author uses the theory of neorealism proposed by Kenneth Waltz regarding the structure of the international system. Then the author uses a qualitative method, namely, the author tries to describe the discussion descriptively by collecting and analysing various literature related to the dispute that occurred. And for the conclusion, the author tries to answer the existing research questions, namely how the Mediterranean dispute can occur and whether there are successful negotiation efforts to reduce the escalation of this conflict. The author hopes that this paper can contribute especially in security and negotiation issues to create a more conducive world through analysing anarchic international structures so that states will act both to pursue and protect their interests in the context of sovereignty where states maintain their existence.